(untitled) (Reflection and Critique Law Magazine, 2020)
The present work aims to address the importance of the victim’s participation in the resolution of conflicts and criminal offenses, under the prism of restorative justice. It is a novel paradigm, based on the culture of dialogue and pacification between offender and offended. Conflict resolution covers not only the legal field, but also several areas, such as harmony between citizens. In this regard, the Anticrime Package came to regularize and implement this policy in specific situations in order to expand consensual justice in the criminal sphere.